Work-Life Balance and Physical Work Environment as Retention Strategy for Health Care Workers - Ekanem, Ekanem Daniel; Agiren, Tuoyo Eresanara (NIU Journal of Social Sciences, 2025)
This study examined how work-life balance and physical work environment serves as retention strategies on Health-care workers, using the University of Benin Teaching Hospital (UBTH) as a case study. The focus was on three key components of retention policies, including work-life balance initiatives, supportive physical work environment, recognition and competitive reward systems. Using Taro Yamane formula, a sample size of three hundred and sixty (366) was arrived out, however, on distribution of the research questionnaire only 360 was found usable for this study. Data was collected through structured questionnaires. The analysis utilized both descriptive statistics such as (frequency, mean, and percentage) and inferential statistics such as (regression analysis) to evaluate the relationships between various variables used. The findings revealed that a physical supportive work environment, and recognition and competitive reward systems significantly enhance organizational performance, with recognition and rewards having the strongest impact on organisational performance. Conversely, work-life balance initiatives were found to have no significant effect. Based on these findings, the study recommends fostering supportive workplaces, and implementing robust recognition systems while reevaluating and redesigning work-life balance initiatives to support the achievements of organizational goals and also meet employee expectations. Keywords: Employee Retention, Organizational Performance, Work-Life Balance, Supportive work environment, and recognition and competitive reward systems